Visual impairment and quality of life, a cross- sectional study - Krasniqi, Marsida; Trebicka, Brunela (International Journal of Psychosocial Rehabilitation, 2020)
Visual impairment and blindness has been a problem for social behavior and public health in the developing countries. Data regarding the influence of visual impairment and blindness in Albania are missing. The aim of our study is to investigate the influence of visual impairment and blindness in quality of their life in Albania. This is a cross-sectional study, conduced in Albania from September 2019 till December 2019. All the patients with eye disease and visual loss were included in this study. The patients have self-completed a questionnaire organized in 3 parts with 18 questions. Gender, age, socio-economic data, eye diseases, level of stress, anxiety and depression were collected in this study and analyzed with SPSS. 871 questionnaires were included in this study according to the criteria. The mean age of the participants in this study was 47.4 years (with a rage from 7 years to 78 years). 40.5% of the participant reported to have anterior segment and refractive disorders followed by diabetic retinopathy and other vascular disorders in 14.3%. 61.3% responded that the quality of vision was with mild visual impairment. Most of the participant reported mild level of anxiety (34%) and depression (30%) and 31% sever stress. the results of our study indicate that visual impairment and blindness have a mild to moderate influence in quality of life and we recommend the start of a rehabilitation program for patients with blindness and visual impairment.